INSTRUMENTAL ASSESSMENT OF PULMONARY FUNCTION IN LATE POST-COVID-19: AN INTEGRATIVE REVIEW (CIPEEX, 2025)
Following the significant impacts of the SARS-CoV-2 pandemic, it is crucial to determine the most effective approach for evaluating pulmonary function in patients who have experienced the disease, as well as to identify the most commonly used instruments for this purpose. This review aimed to analyze the devices used in the assessment of pulmonary function in patients with late COVID-19 phase. This is an integrative review of the scientific literature on this topic. The databases used for data collection were the Biblioteca Virtual de Saude (BVS) and PubMed Unique Identifier (PubMed). The descriptors “Respiratory Therapy,” “Respiratory Function Tests,” and “Post-Acute COVID-19 Syndrome” were used with their corresponding MESH terms in both databases. Articles in English and Portuguese published in the last five years were selected. The search results yielded 17 articles in PubMed and 9 in BVS and the titles, abstracts, and keywords were subsequently analyzed to select the articles to be reviewed. Thus, 3 articles from PubMed and 2 from VHL were included, focusing on the evaluation of pulmonary function using instruments. The results obtained from the analyzed articles indicate that the most common tests for assessing pulmonary function in late post-COVID-19 are spirometry and peak expiratory flow (Peakflow). In spirometry, the values obtained were below normal in all patients who had contracted COVID-19. For patients with an associated respiratory disease, the values for the Forced Vital Capacity (FVC) and Forced Expiratory Volume in the first second (FEV¹) ratio were even lower, approximately 10% lower compared to those without respiratory disease. Reduced vital capacity was observed in more than half of the patients (77.19%), while 22.5% showed spirometric evidence of upper airway obstruction. The Peak expiratory flow results also showed values below normal. Commonly associated with these instruments are the 6-Minute Walk Test, the SF-36 Quality of Life Questionnaire, and Manual Dynamometry. In conclusion, patients in the late post-COVID-19 phase experienced a significant loss of pulmonary function, total lung volume, as well as decreased spirometry results in FEV1 and the FVC/FEV¹ ratio.
Keywords: covid-19; spirometry; lung function; respiratory tests